SPECTRAL PROPERTIES OF TWO WATER-SOLUBLE MELANINS - V.M. Kravchenko; T.V. Beregova; M.Yu. Lositskyi; T.O. Kondratyuk; S.A. Davydenko; E.S. Davydenko; S.S. Davydenko; L.P. Buchatskyi; V.M. Yashchuk (Biotechnologia Acta, 2024)
Aim. The work was purposed to study the spectral properties of two types of water-soluble melanins to clarify the nature of the optical absorption and emission centers in them.